PEMANFAATAN BEE POLLEN SEBAGAI SUMBER ZAT BESI DALAM PEMBUATAN CRACKERS - fitriani, fatimah (Poltekkes Kemenkes Medan, 2021)
Nutritional problems relate directly to the quantity and quality of the food they consume.The research aimed to obtain crackers products that contain amino acids and iron with flour substitution bee pollen (bee pollen). This research was an experimental research with the labolatory analysis design. The research was carried out in three stages: the first stage was an introductory research with laboratory tests on bee pollen flour and organoleptic test, In the product initial research, proximate analysis was conducted, and amino acid content and iron suit of SNI. The research result of crackers formula C2 gives the good preference level. For the product initial research i.e. the proximate analysis, the selected formulas are 7.74% protein and 7.50% for the control formula, 22.81% fat and 21.95% for the control formula 63.61% , carbohydrates and 64.67% for the control formula, water content 3.36% and 3.12% for the control formula, 2.52% ash content and 2.75%. for the control formula. Fe content in bee pollen flour was 145.7862 ppm after being processed into crackers at 88.4402 ppm. This research reveals that the iron decreased after processed into crackers